Human TDP43 is required for ALS?related annexin A11 toxicity in Drosophila. - Barnard, J.; Hunt, R.; Yucel, M.; Mazaud, D.; Smith, B.N.; Fanto, M. (Biomedical reports, 2024)
Genomics allows identification of genes and mutations associated with amyotrophic lateral sclerosis (ALS). Mutations in annexin A11 (ANXA11) are responsible for ~1% of all familial ALS and fronto-temporal dementia cases. The present study used the fruit fly, Drosophila melanogaster, to assess the mechanism of toxicity of ANXA11 mutants in residues that are conserved in the fly ANXB11 protein, the closest homolog to human ANXA11. In immune fluorescence, lifespan and negative geotaxis assays ANXA11 mutants, while displaying some degree of alteration in localization and function, did not exert any relevant organism toxicity in Drosophila. However, they showed a specific interaction with human TAR DNA-binding protein (TDP43). The present study illustrated that the ANXA11 mutants interact with human TDP43, but not the fly TAR DNA-binding protein-43 homolog (TBPH) or other ALS-associated genes such as super oxide dismutase 1, to shorten lifespan and increase negative geotaxis defects. This sheds light both on the mechanisms underlying ALS, further elucidating the intricate molecular network implicated in ALS and placing ANXA11 as a key player in its pathology, and on the complexity of using Drosophila as a model organism for researching genes in ALS.